Synthesis of graphene nanoribbons with a defined mixed edge-site sequence by surface assisted polymerization of (1, 6)-dibromopyrene on Ag(110). Issue 41 (6th October 2016) - Smerieri, Marco; Píš, Igor; Ferrighi, Lara; Nappini, Silvia; Lusuan, Angelique; Di Valentin, Cristiana; Vaghi, Luca; Papagni, Antonio; Cattelan, Mattia; Agnoli, Stefano; Magnano, Elena; Bondino, Federica; et al.
Abstract : Ultra-narrow graphene nanoribbons with selected edge sites are synthesized for the first time by surface assisted polymerisation of pyrene derivatives. Abstract : By a combination of scanning tunneling microscopy, X-ray spectroscopic techniques and density functional theory calculations, we prove the formation of extended patterns of parallel, graphene nanoribbons with alternate zig-zag and armchair edges and selected width by surface-assisted Ullmann coupling polymerization and dehydrogenation of 1, 6-dibromopyrene (C16 H8 Br2 ). Besides the relevance of these nanostructures for their possible application in nanodevices, we demonstrate the peculiarity of halogenated pyrene derivatives for the formation of nanoribbons, in particular on Ag(110). These results open the possibility of tuning the shape and dimension of nanoribbons (and hence the correlated electronic properties) by choosing suitably tailored or on-purpose designed molecular precursors.